PEMBERDAYAAN EKONOMI MASYARAKAT DENGAN SUMBER DAYA ALAM KELAPA SAWIT UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA - Suhela Putri Nasution; Abdurrozzaq Hasibuan; Budhi Santri Kusuma; Syarifah A’ini; Arini Fajriani; Intan Sadillah (Jurnal Pengabdian Mitra Masyarakat, 2023)
Community Empowerment is an economic development concept that encapsulates community values to build a new paradigm in development that is people-centered, participatory. In this context, efforts to empower the community (empowering) can be studied from three aspects, the first is enabling, namely creating an atmosphere that allows the community's potential to develop. Second, empowering, namely strengthening the potential of the community through concrete steps involving the provision of various opportunities that will make the community more empowered. Third, protecting, namely protecting and defending the interests of the weak. Economic empowerment is an effort to become a strong, large, modern and highly competitive economy. The method used in the literature review begins with selecting a topic, then determining keywords to search for journals using Indonesian through the database, namely Google Scholar. Based on several explanations put forward. The main goal of community empowerment is to improve people's welfare through their potential so that they are able to improve a better quality of life through self-help activities.